Pengaruh Latihan Shooting Bola Diam dan Shooting Bola Jalan terhadap Ketepatan Shooting Pemain Usia 15 Tahun Sekolah Sepakbola New Tugumuda Semarang - putra w, guntur soekarno; Sulaiman, Sulaiman (Universitas Negeri Semarang, 2023)
The purpose of this study was to produce a product for developing health education teaching The research objective was to determine whether or not the effect of street and silent shooting training on shooting accuracy as well as to analyze the type of training which was better for shooting accuracy. This type of experiment research uses a group pretest and posttest design. The study population was 24 students of SSB New Tugu Muda u15 Semarang City. The sampling technique used total sampling, so that the sample size was 24 students. The data collection technique used a shooting accuracy test. The data analysis technique used paired-sample t-test and independent-sample t-test. The results obtained information that (1) there is an effect of street ball shooting practice on shooting accuracy, (2) there is an effect of still ball shooting practice on shooting accuracy for players, (3) still ball shooting practice is better than street ball shooting practice on shooting accuracy shooting at a 15 year old player at the NEW Tugumuda Football School Semarang. Conclusion this research is that street ball shooting exercises and stationary balls have an effect on shooting accuracy and still ball shooting exercises are better than street ball shooting exercises.